USER PERCEPTION AND PREFERENCE STUDY ON BATIK MOTIFS FOR USE IN UPCYCLED PRODUCTS - Angelika, Amelia (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2024)
User perception and preference play a crucial role in accepting upcycled products, with 85% of respondents valuing aesthetics as a key factor. The waste fabric is processed through creative innovation and upcycling to enhance its value. Batik was chosen for its cultural significance, with Buketan motifs as an example of motif application. This study examines user perceptions and preferences regarding Batik motifs on upcycling products, focusing on aesthetics and functionality. An online survey gathered responses from 68 female participants aged up to 35. Thematic analysis identified patterns in user views related to aesthetics, functionality, and cultural value. Findings suggest that Batik motifs can enhance the visual appeal of upcycled products and add cultural identity, though some motifs may lack versatility. While users see market potential, premium pricing could limit acceptance. This highlights the importance of balancing creative product development with sustainable thinking and customer acceptance to enhance the appeal of upcycled products with batik-based aesthetics.